1993
DOI: 10.1042/bj2910179
|View full text |Cite
|
Sign up to set email alerts
|

Expression of rat liver ketohexokinase in yeast results in fructose intolerance

Abstract: Rat liver ketohexokinase (ATP:D-fructose 1-phosphotransferase; EC 2.7.1.3) was purified to homogeneity and the molecular mass of the protein was found by mass spectrometry to be 32,800 Da. The enzyme was cleaved and the amino acid sequences of seven peptides, comprising 24% of the total sequence, were determined. This sequence information was used to design oligonucleotide primers for a PCR using rat liver single-stranded cDNA as a template. The 224 bp PCR product was used as a probe to screen a rat liver cDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…The primary structure of rat liver KHK was, however, recendy described (5). This work demonstrated that KHK is structurally unlike other mammalian hexokinases, and does not show significant homology with other known mammalian protein families.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The primary structure of rat liver KHK was, however, recendy described (5). This work demonstrated that KHK is structurally unlike other mammalian hexokinases, and does not show significant homology with other known mammalian protein families.…”
Section: Introductionmentioning
confidence: 86%
“…Val49De, on the other hand, does not produce fructosuria when present in the homozygous state, and is a common polymorphism in normal Europeans (data not shown). Finally, under the rather unlikely null hypothesis that essential fructosuria could result from a mutation unlinked to KHK, the concordant segregation between the mutations and the fructosuria in this family has a probability of only (U) 2 (K) 5 (excluding one proband) » 1 in 67.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In its active form, it is a dimer [3] and requires K ϩ and ATP for activity. The physiological substrate for hepatic KHK is D-fructose, derived from dietary fructose, sucrose, or sorbitol, but it can also phosphorylate D-xylulose [1,3].Although most abundant in the liver, KHK is also found in kidney, small intestine and pancreas [2] and at much lower levels in heart, brain and muscle [3]. The distribution of highexpressing tissues is generally consistent with a major role in…”
mentioning
confidence: 99%
“…This pathway metabolises fructose to the glycolytic intermediate glyceraldehyde-3-phosphate, in the process bypassing the important regulatory phosphofructokinase/fructose bisphosphatase step of glycolysis. KHK is most abundant in the liver, where it constitutes between 0.04% and 0.6 % of total protein [1,2]. The enzyme has been purified from human [3], bovine [1] and rat liver [2].…”
mentioning
confidence: 99%